Reshaping 'time of limbo' and 'remoteness': Everyday practices of reception of asylum seekers in Alpine municipalities in Italy. Issue 2 (1st October 2021) - Giacomelli, Elena; De Gregorio, Orlando
This article focuses on the experiences of widespread reception of asylum seekers and refugees carried out in some Italian Alpine localities, specifically in Valsugana in Trentino and Val di Susa in Piemonte, in the west and in the east of northern Italy. We focus on the description of these two case studies and their relation with the frame of national policies on migration in Italy. What were the main characteristics of these two case studies? How do these local policies interact with the fragmentation, the inconsistency and the emergency-based approach of Italian national immigration policies? This research subsumes and aims to move beyond the questions raised above, focusing on the points of view and narratives of social workers, project managers and reception workers (operatore dell'accoglienza). These actors often describe the implementation process as a process of policy-making. In conclusion, these case studies highlight that in Italy good practices of reception represent a field where there are coordinations, tensions and conflicts between national and local levels. Indeed, in everyday practices, the limbo and isolation (characterizing the life of asylum seekers) are reshaped in inclusion paths. This daily process of policy-making is constantly at risk ‐ in Italy, indeed, good practices of inclusion represent a battlefield criss-crossed by dilemmas.